Pioneers vs. Occidental College Saturday, Sept. 27, 1969 - California State College, Hayward Athletics:::::: (1969)
Program for the September 27, 1969 football game between the California State College, Hayward Pioneers and Occidental College. Includes future football schedules, team rosters and probable starting lineups, photographs of CSCH players and coaches, schedules for other CSCH sports, and the CSCH alma mater.